ANALISIS BEBAN KERJA DENGAN METODE RULA PADA DIVISI PEMINDAHAN BARANG DI PT. NUSANTARA CARD SEMESTA CABANG MEDAN - Ardiansyah Tanjung; Nabila Yudisha; M. Fiza Lubis (Bajang Institute, 2026)
PT. Nusantara Card Semesta is a company engaged in the delivery of goods that cannot be separated from problems related to work postures. This can be seen by the wrong posture and working methods of the workers in the transfer of goods division which can result in muculoskeletal injuries, thereby reducing work productivity. Therefore, it is necessary to analyze the workload of workers in the transfer of goods division to obtain an effective work posture in doing work so that an employee can carry out his work activities according to his ability or work capacity. Rapid Upper Limb Assessment (RULA) is a method to assess posture, style, and movement of a work activity related to the use of the upper body (upper limb). This method was developed to investigate the risk of abnormalities that will be experienced by a worker in carrying out work activities that utilize the upper limb. The first step in analyzing the workload using the RULA method is to analyze the current work posture, which is then followed by an analysis of the work postures that can cause injury. After obtaining a work posture that can cause injury, problem solving is carried out with a proposed design of a work posture that is comfortable and does not cause injury. The conclusion that can be drawn from the workload analysis using the RULA method is that the work posture that has the highest risk is the work posture of lifting goods from the warehouse to the transport truck. This condition shows that the work posture in the moving goods division has a very large risk of abnormalities that can result in musculoskeletal injuries so that it can reduce work productivity. Keywords: RULA, musculoskeletal, workload analysis